(untitled) - Papalia, Diane E. (Boston, 2004)
Human development, 9th ed., continues to provide a well-written, chronological view of lifespan development. It combines up-to-date coverage of research with applications and real-life examples that appeal to nursing and educatuon students, as well as parents. The text includes coverage of social policy, cross-cultural topics, and current health.
Keywords: Developmental psychology,Developmental psychobiology